Mineralogy : an introduction to minerals, rocks, and mineral deposits - Okrusch, Martin. 1934-; Frimmel, Hartwig E. (Berlin, Germany : Springer, 2020)
This book presents a translation and update of the classic German textbook of Mineralogy and Petrology that has been published for decades. It provides an introduction to mineralogy, petrology, and geochemistry, discussing the principles of mineralogy, including crystallography, chemical bonding, and physical properties, and the genesis of minerals in a didactic and understandable way. Illustrated with numerous figures and tables, it also features several sections dedicated to the genesis of mineral resources. The textbook reflects the authors many years of experience and is ideal for use in lectures on mineralogy and petrology.
Includes bibliographical references and index.
Keywords: Mineralogy; Geochemistry; Geology, Economic